Assessing the Effects of Land Use Practices on the Environment in Rugarama North Ntungamo District. - Turyahabwe, Deus (2025)
This study was focused on assessing the effects of land use practices and environment in Ntungamo district. The study was guided by three objectives; to identify effects of land use practices on environmental conservation in Rugarama sub-county Ntungamo district, to establish policies/laws that govern land and environment in Rugarama sub-county Ntungamo district and to identify the activities that degrade the environment in Rugarama sub-county Ntungamo district. Data collection tools included questionnaires and interview guide which were used to collect data from 100 respondents mainly staff of Rugarama sub-county, leaders and community members. Data analysis was done using Microsoft excel and the findings were presented in tables, charts and graphs. The study findings indicates that there were policies/laws that govern land and environment as they include; national land use policy with 14%, national environment Act with 20%, the land Act of 1998 with 10%, the Uganda national land policy 2013 with 16% and local policies or rules that govern land and environment with 40%. Majority of the respondents with 40% agreed that local policies or rules that govern land and environment were the major policy used by respondents from Rugarama Sub-county Ntungamo district. Findings of the study indicates that there were effects of land use practices on environment as they include; Good quality yields indicated by 18%, Increased Quantity yield or yield per acre presented by 20%, improved soil fertility presented by 36% and other factors with 26%. However majority of the respondents revealed that improved soil fertility with 36% was the most common effect affecting land use practices in Rugarama sub-county Ntungamo district. The study findings indicates that there were activities that degrades the environment which include; overpopulation with 16%, housing/settlement with 8%, land tenure with 4%, overgrazing with 12%, bush burning with 10%, over cultivation with 22%, mono cropping with 20% and other factors with 8%. However majority of the respondents revealed that over cultivation with 22% was the major activity that degrade the environment. The study concludes that there were activities that degrades the environment which include; Over population, Housing/settlement, Land tenure, Over grazing and Deforestation. The study recommends that; there is need for farmers to apply manures and fertilizers in order to get high quality and quantity yields. The use of farmyard manure should be encouraged to restore soil fertility. This should be done along with good husbandry practices such as crop rotation, and rotational grazing to avoid exhausting a particular plot of land in a short period, which in most cases forces people to encroach lands. There is need for policy making concerning environmental conservation measures through a forestation thus discouraging or reducing deforestation and education of masses should be encouraged relating to the efficient use of land use practices on environment through sensitizing people on dangers of mining and mining related effects.